2022
DOI: 10.1051/0004-6361/202142790
|View full text |Cite
|
Sign up to set email alerts
|

The Fornax3D project: The environmental impact on gas metallicity gradients in Fornax cluster galaxies

Abstract: The role played by environment in galaxy evolution is a topic of ongoing debate among astronomers. There has been little success in elucidating the degree to which environment can alter, re-shape, or drive galaxy evolution, that is, using either observations or simulations. However, our knowledge of the effect of environment on gas metallicity gradients remains limited. Here we present our analysis of the gas metallicity gradients for a sample of ten Fornax cluster galaxies observed with MUSE as part of the Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 134 publications
1
4
0
Order By: Relevance
“…The gas metallicity estimated through strong emission lines give important clues on the physical properties of the ISM and formation and growth of galaxies. Negative gas metallicity gradients are widely found in late-type galaxies in the local universe (e.g., Zaritsky, Kennicutt & Huchra 1994;Pilyugin et al 2004;Moustakas et al 2010;Pilyugin et al 2014;Belfiore et al 2017;Lara-López et al 2022). Such negative gradients are consistent with an inside-out growth scenario of the discs (e.g.…”
Section: Oxygen Abundance Gradient and Supernova Remnantssupporting
confidence: 63%
“…The gas metallicity estimated through strong emission lines give important clues on the physical properties of the ISM and formation and growth of galaxies. Negative gas metallicity gradients are widely found in late-type galaxies in the local universe (e.g., Zaritsky, Kennicutt & Huchra 1994;Pilyugin et al 2004;Moustakas et al 2010;Pilyugin et al 2014;Belfiore et al 2017;Lara-López et al 2022). Such negative gradients are consistent with an inside-out growth scenario of the discs (e.g.…”
Section: Oxygen Abundance Gradient and Supernova Remnantssupporting
confidence: 63%
“…Metallicity has been suggested as a factor in SN Ia variation (D'Andrea et al 2011;Childress et al 2013), and the deep gravitational potential well at the centers of galaxy clusters should retain metals better than field quiescent galaxies. However, studies of low-redshift cluster galaxies show they are only slightly more metal-rich (0.05 dex) than field counterparts (Ellison et al 2009;Lara-López et al 2022). Observations of the intracluster medium do show a metal enhancement near low-z cluster centers (Lovisari & Reiprich 2019), but the metals escape the galaxies (and subsequent generations of stars) similarly to field quiescent galaxies.…”
Section: Discussionmentioning
confidence: 94%
“…As such, we believe that our analysis would deeply benefit if supplemented with spectroscopic data, which would provide additional insight on the stellar populations (and also the dynamics) of the galaxies. Several studies have already shown how Integral Field Unit spectroscopy can be used to thoroughly dissect and extract the properties of galaxies of the Fornax cluster (Iodice et al 2019;Johnston et al 2020;Lara-López et al 2022), including dwarf galaxies. This is something we would like to incorporate in our future work.…”
Section: Implications Of Substructure Colormentioning
confidence: 99%